(untitled) (Research, Society and Development, 2022)
People with multiple sclerosis (MS) commonly present negative impacts on activities of daily living (ADLs) with the disease progression. However, there is no instrument with measured metric properties specifically for use in people with MS. Objective: To verify the reproducibility and validity of the Londrina ADL Protocol (LAP) to assess ADLs in people with MS. Methods: Individuals diagnosed with ME presenting mild or moderate disability according to the Expanded Disability Status Scale (EDSS) performed the LAP in three moments (intra-rater and inter-rater) following standardized recommendations. Physical activity level was used as validation criterion and was assessed by the pedometer which counts steps/day during seven consecutive days. Results: Twenty-three individuals (48% women, 39 ± 9.2 years, diagnosis time: 9.9 ± 5.5 years) with EDSS 2.5±1.0 points were included. The LAP was reproducible intra-rater and inter-rater (Intraclass Correlation Coefficient [ICC] = 0.86 and 0.72, respectively); however, participants demonstrated a learning effect of -6.6 ± 8.4%. There was a significant correlation between the LAP and the number of steps/day (r = -0.556, p = 0.014). Conclusion: The Londrina ADL Protocol is a promised reproducible and valid instrument that can be used for the objective assessment of ADLs in people with MS.